Implications of seed coat cracking on soybean seed quality - Sheila Bigolin Teixeira; Maria de Fátima Zorato; Geri Eduardo Meneghello (Journal of Seed Science, 2024)
ABSTRACT: Seed coat cracking is a “physiological defect” that occurs in soybean seeds, affecting their integrity. The objective of this study was to evaluate the effect of seed coat cracking on the physiological quality and storability of soybean seeds. Seeds from three lots were used: one from the NS 7209 IPRO cultivar and two from the 8473 RSF cultivar, produced in the states of Goiás and Mato Grosso, Brazil. Each lot was manually segregated into three portions: the original lot (OL), seeds with an intact seed coat (IS), and seeds with a cracked seed coat (CS), which were stored at temperatures of 15 °C and 28 °C for 270 days. The experiment was carried out in a completely randomized design. Vigor and viability were evaluated using the tetrazolium test, first germination count, germination test, accelerated aging, and electrical conductivity at 0, 45, 90, 135, 180, 225, and 270 days of storage, as well as seedling emergence in a seedbed after 0, 90, 180, and 270 days of storage. Seed coat cracking in soybean reduced the physiological quality of the lots in all the tests compared to seeds with intact seed coats, and this effect was more pronounced when seeds were stored at 28 °C. Seed coat cracking contributes to increased seed deterioration in soybean when seeds are stored under high-temperature conditions.